Estimating the Impact of North-South and South-South Regional Trade Agreements on South African bilateral trade - MCHANI, SIBULELE (Economica, 2024)
Based on the gravity model, this paper aimed to evaluate the impact of three regional trade agreements on South Africa’s bilateral trade with thirty-eight countries. Ordinary least squares (OLS) was employed as an estimator of the gravity model. The results demonstrate that the SACU-MERCOSUR preferential trade agreement and EU-SADC free trade agreement are positive and statistically significant. While the SACU-EFTA free trade agreement increases trade intensity by 2.4-fold, the EU-SADC free trade agreement enhances it 2.6-fold. In other words, the participation of South Africa and a respective trade partner in the SACU-EFTA trade agreement improve their bilateral trade by 2.4-fold, while their membership in the EU-SADC free trade agreement raises bilateral trade by 2.6-fold.